2020
DOI: 10.1186/s13046-020-01737-1
|View full text |Cite
|
Sign up to set email alerts
|

Targeting HMGB3/hTERT axis for radioresistance in cervical cancer

Abstract: Background Radiotherapy is regarded as a milestone for the cure of cervical cancer. However, clinical outcome heavily be hindered by radioresistance. So, exploring the underlying mechanism of radioresistance, and find potential target, well deserve fully emphasis. Methods In this study, we developed two novel radiation resistance cervical cancer cell lines, which could mimic clinical radioresistance. In order to find new potential targets, RNA-Seq,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 50 publications
(58 reference statements)
1
24
0
Order By: Relevance
“…Silencing of GRP94 in CC cells induced increased sensitivity to radiotherapy [27]. Besides, Zou found that depletion of HMGB3 signi cantly enhanced the radio-sensitivity of CC cells, while overexpression of HMGB3 had the opposite effect; this effect was mediated via transcriptional upregulation of hTERT [28]. The present study found a correlation between high level of HNF1α and radio-resistance of CC tissues.…”
Section: Discussionsupporting
confidence: 62%
“…Silencing of GRP94 in CC cells induced increased sensitivity to radiotherapy [27]. Besides, Zou found that depletion of HMGB3 signi cantly enhanced the radio-sensitivity of CC cells, while overexpression of HMGB3 had the opposite effect; this effect was mediated via transcriptional upregulation of hTERT [28]. The present study found a correlation between high level of HNF1α and radio-resistance of CC tissues.…”
Section: Discussionsupporting
confidence: 62%
“…Notably, HMGB3 is highly expressed and plays a vital role in the malignant progression of a variety of cancers [ 8 ]. Overexpressed HMGB3 is closely related to tumor occurrence and reduced survival in cervical cancer [ 12 ], non-small-cell lung cancer [ 13 ], breast cancer [ 14 ], bladder cancer [ 15 ], hepatocellular carcinoma [ 16 ], colorectal cancer [ 17 ], gastric cancer [ 18 ], and leukemia [ 19 , 20 ]. However, the expression pattern and clinicopathological characteristics of HMGB3 in high-grade serous ovarian carcinoma (HGSOC) have not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…HMGB3 also participates in the regulation of chemotherapy resistance for several tumors. Li et al observed that HMGB3 transcriptionally activates human telomerase reverse transcriptase (hTERT) and promotes the DNA damage response, contributing to the development of radioresistance in cervical cancer [ 12 ]. HMGB3 has been revealed to be targeted by miR-27b and is associated with tamoxifen resistance in breast cancer [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Loss of CIRBP expression is correlated with the malignant progression and poor prognosis in nasopharyngeal carcinoma [29]. Among the 11 coding genes, HMGB3 was widely reported to promote malignant progress and predict poor survival in various cancer types [30][31][32]. In addition, Gu et al reported that HMGB3 silence could inhibit the cell proliferation in vitro and suppress tumor growth in vivo levels.…”
Section: Discussionmentioning
confidence: 99%